Конституції Польщі 1921 та 1935 років в українській та польській історіографії - Булавіна, С.; Bulavina, S. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
Проаналізовано праці польських, українських та російських істориків держави і права, а також нормативно-правову базу – Конституції Польської Республіки 1921 та 1935 років, закони і розпорядження, які стосувалися історії становлення та розвитку державно-правових інститутів у 1918–1939 роках. В умовах нинішньої реформи політичної системи і формування правової держави в Україні слід використати історичний досвід Польщі в розбудові держави, щоб не допустити помилок, які призвели до встановлення авторитарної системи в Польщі наприкінці 20-х – всередині 30-х рр. ХХ ст. The article is devoted to the analysis of the works of the Polish, Ukrainian, and Russian historians specializing in a state and law, and the normative legal basis - the Constitutions of the Polish Republic of the 1921 and 1935, laws and orders connected with the history of the formation and development of the state and legal institutions in 1918–1939. A special attention has been paid to the historical legal literature and the works published before 1939, scientific studies of the Soviet period and the studies of the post-Soviet time. The author underlines that the analysis of the historical and historical legal literature, and the related documents gives the right to state that the complex studies of this problem would join the efforts of many scientists from various countries and of different historical periods and would fill in the blanks in the modern historical legal science.
Constitutions of Poland of the 1921 and 1935 Represented in the Ukrainian and Polish Historiography
Keywords: закони; конституції; дослідження; історіографічна база; нормативно-правова база; laws; constitution; studies; historiographic basis; normative legal basis